2016
DOI: 10.1007/s11064-016-2044-4
|View full text |Cite
|
Sign up to set email alerts
|

AKT/GSK3β Signaling in Glioblastoma

Abstract: Glioblastoma (GBM) is the most aggressive of primary brain tumors. Despite the progress in understanding the biology of the pathogenesis of glioma made during the past decade, the clinical outcome of patients with GBM remains still poor. Deregulation of many signaling pathways involved in growth, survival, migration and resistance to treatment has been implicated in pathogenesis of GBM. One of these pathways is phosphatidylinositol-3 kinases (PI3K)/protein kinase B (AKT)/rapamycin-sensitive mTOR-complex (mTOR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 61 publications
4
77
0
Order By: Relevance
“…AKT not only stabilizes cyclin D1 by phosphorylation and inactivation of GSK3β but also directly inhibits p21 and p27 [33,34]. Moreover, as a downstream effector, GSK3β can also regulate cyclin D1 [15,22,44], while GSK3β inhibition increases the level of p21 and downregulates CDK and p-RB, which can block cell cycle progression [32,33]. In this study, we demonstrated that peiminine significantly inhibits phosphorylation of AKT and GSK3β in GBM cell lines (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…AKT not only stabilizes cyclin D1 by phosphorylation and inactivation of GSK3β but also directly inhibits p21 and p27 [33,34]. Moreover, as a downstream effector, GSK3β can also regulate cyclin D1 [15,22,44], while GSK3β inhibition increases the level of p21 and downregulates CDK and p-RB, which can block cell cycle progression [32,33]. In this study, we demonstrated that peiminine significantly inhibits phosphorylation of AKT and GSK3β in GBM cell lines (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…As is well known, the protein kinase B (AKT)-glycogen synthase kinase 3β (GSK3β) pathway controls many intracellular processes involved in cancer cell growth, proliferation, angiogenesis, metabolism and motility in GBM [14,15]. Many studies have shown that inhibiting the AKT pathway and its downstream effector, GSK3β, reduced the growth of GBM cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, protein phosphatases also may influence GSK3β phosphorylation through the Akt pathway (Millward et al, 1999; Bononi et al, 2011). In the Akt pathway, stimulation of the phosphoinositide 3-kinase/Akt pathway leads to activation of Akt via phosphorylation of T308 and S473 residues, and then active Akt phosphorylates GSK3β/α at S9/21 (Gold et al, 2000; Varea et al, 2010; Majewska and Szeliga, 2016). Protein phosphatases (in particular protein phosphatase 2A) dephosphorylate Akt leading to Akt inactivation, and subsequently increased active GSK3β/α via the loss of Akt-mediated S9/21 phosphorylation (Millward et al, 1999; Bononi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S9/S21 phosphorylation leads to inactivation because the N-terminus of GSK3 competitively blocks substrate docking in the primed substrate pocket (Frame et al, 2001) acting as a dominant negative regulator of GSK3 activity, especially against substrates requiring priming. In situ , GSK3 is regulated, at least in part, by phosphorylation at S9 from Akt leading to reduced activity (Gold et al, 2000; Varea et al, 2010; Majewska and Szeliga, 2016) and protein phosphatases that dephosphorylate S9 leading to increased activity under several biological contexts (Sutherland et al, 1993; Leung-Hagesteijn et al, 2001; Morfini et al, 2004; Lee et al, 2005; Szatmari et al, 2005; Bertrand et al, 2012). However, the lack of reagents that specifically detect nonphospho-S9 (npS9) GSK3 has limited our ability to directly study dephosphorylation of this N-terminal serine.…”
Section: Introductionmentioning
confidence: 99%
“…mTOR is a Ser/Thr kinase that belongs to the phosphoinositide kinase-related family of protein kinases (PIKKs). mTOR acts as an essential integrator of growth-factor-activated and nutrient-sensing pathways to control and coordinate various cellular functions, including survival, proliferation, differentiation, autophagy and metabolism (8)(9)(10)(11) This article is freely accessible online. *These authors contributed equally to this study.…”
mentioning
confidence: 99%